Use of confocal Raman imaging to understand the microstructure of anhydrous milk fat-based oleogels. (October 2021) - Gómez-Mascaraque, Laura G.; Tran, Caine; O'Callaghan, Tom; Hogan, Sean A.
Abstract: This work explores confocal Raman microscopy as a novel approach to study the microstructure of oleogels, using milk fat-based oleogels as a case study. Anhydrous milk fat (AMF) was sequentially fractionated to obtain two olein and two stearin fractions with different thermal properties. These and the unfractionated AMF were structured into oleogels using ethyl cellulose as gelling agent. Although the fatty acid profile of the different fractions showed only minor changes (in most cases < 10% change), the microstructure of the various oleogels was markedly different, especially the unfractionated AMF based oleogels, which exhibited distinct pseudo-spherical features suggesting segregation of components. Different univariate and multivariate data analysis approaches, were compared to map the distribution of components in the oleogels using confocal Raman microscopy. The univariate approach only provided accurate microstructural information for oleogels prepared with olein (liquid at the temperature of analysis). The multivariate approaches, although more complex, provided reliable results for all oleogels. Mapping lipids with different degrees of mobility (liquid vs solid) within the oleogels was possible with this technique. Solid lipids were located preferentially in close proximity to ethyl cellulose, and were confirmed to be the main component of the microspheres found in the unfractionated AMF oleogels. Graphical Abstract: ga1 Highlights: Small variation in fatty acids led to significant structural differences in oleogels. Raman microscopy allowed distinguishing lipids with different degrees of mobility. Segregation of solid lipids was observed in oleogels prepared with unfractionated fat. Fat with low mobility preferentially located in close proximity to ethyl cellulose. Multivariate data analysis provided more structural information in complex oleogels.